Dramaturgi Pengguna Second Account pada Media Sosial Instagram - Azri Inda Robbi; Dian Widya Putri (Bandung Conference Series: Communication Management, 2024)
Abstract. The era of society 5.0 is an era of life that is centered on and dependent on technology. The presence of social media has become an important element that can make human life easier today. One of the most popular social media today is Instagram. Instagram is the second most popular social media network among Indonesian people. Instagram has become a part of generation z's daily life. The emergence of Instagram was also accompanied by the second account phenomenon which made the Instagram application increasingly popular. The aim of this research is to find out more about managing the impression of using a second Instagram social media account on social interactions in Generation Z in terms of dramaturgical theory. This research uses qualitative research methods with a dramaturgical theory approach from Erving Goffman. The data collection techniques used by researchers are interviews, observation and documentation. Informants were taken using snowball sampling in the generation z environment in Bandung City. The results of this research are in accordance with Erving Goffman's dramaturgical theory, there are differences in personality on the front stage and the back stage. In managing these two stages, informants utilize the front stage through their first account to build the best self-image from their personal life, while the back stage, represented by the second account, is used to share more personal experiences. Therefore, by carefully managing your personality you can maintain a balance between maintaining your self-image and showing other sides of yourself in their environment. Abstrak. Era society 5.0 merupakan era kehidupan yang berpusat dan ketergantungan pada teknologi. Kehadiran media sosial telah menjadi salah satu elemen penting yang dapat memudahkan kehidupan manusia saat ini. Salah satu media sosial yang paling populer saat ini adalah Instagram. Instagram menjadi jaringan media sosial terpopuler kedua di kalangan masyarakat Indonesia. Instagram telah menjadi bagian dari kehidupan sehari-hari generasi z. Munculnya Instagram juga dibarengi dengan fenomena second account yang membuat aplikasi Instagram semakin populer. Tujuan dari penelitian ini untuk mengetahui lebih dalam mengenai pengelolaan kesan penggunaan second account media sosial Instagram terhadap interaksi sosial pada generasi z yang ditinjau dari teori dramaturgi. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan teori dramaturgi dari Erving Goffman. Teknik pengumpulan data yang digunakan peneliti adalah wawancara, observasi, dan dokumentasi. Pengambilan informan menggunakan snowball sampling di lingkungan generasi z di Kota Bandung. Hasil dari penelitian ini sesuai dengan teori dramaturgi Erving Goffman terdapat perbedaan kepribadian pada panggung depan (front stage) dan panggung belakang (back stage). Dalam mengelola kedua panggung tersebut informan memanfaatkan panggung depan (front stage) melalui first account mereka untuk membangun citra diri yang terbaik dari kehidupan pribadi, sedangkan panggung belakang (back stage) yang diwakili second account digunakan untuk berbagi pengalaman yang lebih pribadi. Oleh karena itu dengan mengelola kepribadian secara cermat dapat menjaga keseimbangan antara menjaga citra diri dan menampilkan sisi lain pada diri sendiri di dalam lingkungan mereka.